Factors influencing students' performance in medical microbiology in Univeristy of Ilorin, Ilorin, Nigeria (2010)
Excellent performance by students, in any discipline, depends on a number of factors. We determined teachers and students' factors influencing students' performance in Medical Microbiology, using University of Ilorin Medical programme as a case study. Medical students who had completed at least 2 postings in pathology were selected and interviewed using a self administered questionnaire. A total of 173 students were interviewed among which 119 (68.8%) were males while 54 (31.2%) were females. Majority of the students (81.5%) believed that Medical Microbiology lecturers have the required professional teaching qualities, 82.1% also agreed that the lecturers were interested in their subject. However, 60.4% agreed that the lecturers use poor teaching methods and 55.5% agreed that lecturers teach Microbiology in abstract terms. Cultism and social activities (53,9%), Students' failure in scheduling their time wisely (64.7%), failure to take their practical session seriously (55.5%) and lack of appropriate books (69.9%) affected students' performance negatively. From our study, it was discovered that the use of poor teaching methods, excessive work load and failure of students to manage time appropriately were major factors negatively influencing Medical student's performance in: Medical Microbiology while lecturer's qualification and interest would affect their performance positively in the same subject if properly harnessed. For optimal performance, we recommend the reorganization of pathology training programme to include lectures enhanced with multimedia projection and illustrations, laboratory rounds, role play, teaching rounds and Tutorials.